Integrated radome and antenna systems of low radar cross section - Li, Mengyao (Nanyang Technological University, 2024)
Frequency selective structures (FSS) are widely used in antenna radome systems due to their spatial filtering characteristics. One of the most practical applications of FSS is to reduce the undesired radar cross section (RCS) of antenna systems by manipulating electromagnetic waves. In practical applications, the antenna should maintain communication with high radiation efficiency in the interested frequency band, which may be a trade-off with the low-RCS properties. Therefore, it is desirable that the scattering from the antenna be controllable out of the antenna operating frequency band. There are several techniques to reduce the RCS of an antenna, such as using a distributed loading, employing absorptive materials as antenna radome, and applying diffusive chessboard surfaces to realize destructive interference. On the one hand, these conventional techniques are limited by some drawbacks, such as operating bandwidth, increased insertion loss, and limited frequency responses to electromagnetic waves. On the other hand, the radiation gain is also a critical concern in many communication systems to improve the signal-to-noise ratio. To enhance the gain of an antenna, the effective method is to increase antenna’s aperture size. However, the increased aperture will lead to larger RCS inevitably. Therefore, it is desired to design an antenna integrated with radome system, which has both high-gain radiation and low-RCS characteristics. The main concept of designing the frequency selective radomes with a transmission window for antenna radiation within an RCS reduction frequency band is to merge multiple resonances into a unit cell of a periodic structure. According to this, two types of frequency selective radome with a diffusion-transmission-diffusion and an absorption-transmission-absorption frequency response, respectively, are proposed. Both of them alleviate to some extent the limitations suffered by existing radomes. Simulation and measurement results demonstrate the effectiveness of the design concept and potential applications of the radomes in antenna systems expecting a low out-of-band scattering, while maintaining a good in-band transmission performance. In addition, a slot antenna array and two polarization converters are co-designed as an antenna-radome system (ATRS). Different from the classical approaches of placing the radomes far away from the antenna to ensure a free space environment for both the antenna and radomes, such design is a novel attempt to integrate a diffusive radome with an antenna array. Therefore, a low-profile antenna-radome is achieved. As a result, the radiation properties of the antenna array are well maintained, while the undesired scattering waves are diffused into other directions. Full-wave simulations and experiments indicate that high-gain radiation is obtained by using an antenna array and the out-of-band backscattering is significantly reduced based on destructive interference. The research on the low-RCS frequency selective radomes is further extended to the transmission phase response to explore another effective strategy to enhance the radiation gain in a low-RCS antenna system. Following to this motivation, a unit cell with an absorption-transmission-absorption frequency response and a controllable transmission phase response is proposed. In order to simplify the structure and extend the phase shifting range, a cross-polarization converter is integrated into the unit cell, which provides a maintained high transmission magnitude and varying phases in its transmission frequency band. Therefore, it is a good candidate to achieve beam manipulations such as beam steering and beam focusing. A low-RCS transmitarray composed of the proposed unit cells is designed. It is demonstrated that a focused beam with high gain and low-RCS signature at two-sided frequencies are achieved simultaneously. Therefore, such a design can be a good strategy to reduce the RCS of a high-gain antenna. The design concept of the low-RCS transmitarray is further applied to a conformal platform. The phase-shifting components are designed based on an all-metal structure, which is able to be fabricated as any shape. In addition, a lossy layer printed on an ultra-thin substrate, which is easy to be curved, is integrated to provide the absorption frequency response. The integrated unit cell is miniaturized to alleviate the degradation to the predicted response under an oblique incidence. To verify the effectiveness of the design concept, a cylindrical transmitarray aperture is proposed. As a result, an enhanced radiation gain is achieved by phase compensation in the operating frequency band and the dual-polarized RCS reduction is achieved at other frequencies. Such structure is a novel attempt to design a conformal low-RCS transmitarray for more practical application scenarios. In summary, this thesis explores the techniques to design integrated ATRSs with a significant RCS reduction. Meanwhile, considering the possible degradation of the radiation gain caused by the added radomes, the strategies to enhance the radiation gain are also discussed in the low-RCS systems. Finally, a few recommendations are made for further research perspectives with more challenges to be attempted.